Vegfr3-tdTomato, a reporter mouse for microscopic visualization of lymphatic vessel by multiple modalities. - Esther Redder; Nils Kirschnick; Stefanie Bobe; René Hägerling; Nils Rouven Hansmeier; Friedemann Kiefer (PLoS ONE)
Lymphatic vessels are indispensable for tissue fluid homeostasis, transport of solutes and dietary lipids and immune cell trafficking. In contrast to blood vessels, which are easily visible by their erythrocyte cargo, lymphatic vessels are not readily detected in the tissue context. Their invisibility interferes with the analysis of the three-dimensional lymph vessel structure in large tissue volumes and hampers dynamic intravital studies on lymphatic function and pathofunction. An approach to overcome these limitations are mouse models, which express transgenic fluorescent proteins under the control of tissue-specific promotor elements. We introduce here the BAC-transgenic mouse reporter strain Vegfr3-tdTomato that expresses a membrane-tagged version of tdTomato under control of Flt4 regulatory elements. Vegfr3-tdTomato mice inherited the reporter in a mendelian fashion and showed selective and stable fluorescence in the lymphatic vessels of multiple organs tested, including lung, kidney, heart, diaphragm, intestine, mesentery, liver and dermis. In this model, tdTomato expression was sufficient for direct visualisation of lymphatic vessels by epifluorescence microscopy. Furthermore, lymph vessels were readily visualized using a number of microscopic modalities including confocal laser scanning, light sheet fluorescence and two-photon microscopy. Due to the early onset of VEGFR-3 expression in venous embryonic vessels and the short maturation time of tdTomato, this reporter offers an interesting alternative to Prox1-promoter driven lymphatic reporter mice for instance to study the developmental differentiation of venous to lymphatic endothelial cells.